Application of Time Series Analysis and Geographic Information System (GIS) in Forecasting the At-Risk areas of Dengue in Cavite, Philippines - Glenn Bryan A. Creencia, John Daniel V. Cap-atan, Charles Vincent Boral, Mildred A. Sebastian (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Cavite declared a province-wide dengue outbreak from the year 2015 to 2018. The study helped create maps of the number of cases of dengue in the 16 municipalities and 7 cities of Cavite from 2003 to 2020; determined the predictors of dengue cases in terms of age and sex of the patients; and predicted the dengue cases in the year 2022, 2024, and 2026. The dengue cases and patients' profiles from 2003 to 2020 in Cavite were obtained from the Provincial Epidemiology Surveillance Unit (PESU). The maps of dengue cases from 2003 to 2020 and the predicted cases of dengue in the year 2022, 2024, and 2026 were created using ArcMap 10.4. Time series analysis was used to predict the dengue cases in Cavite in the years 2022, 2024, and 2026. Based on the results, the highest dengue case was recorded in Dasmarinas City, followed by Bacoor City, Imus City, Gen. Trias City, and TreceMartires City. In 2022, the forecasted dengue cases in Dasmarinas City are 1,995; 1,352 in Imus City; and 1,260 in Bacoor City. In 2024, the forecasted dengue cases in Dasmarinas City are 2,228; 1,514 in Imus CIty; and 1,398 in Bacoor City. In 2026, the forecasted dengue cases in Dasmarinas City are 2,460; 1,676 in Imus City, and 1,537 in Bacoor City. Dasmarinas City, Imus City, and Bacoor City in the province of Cavite are at risk of dengue in the years 2022, 2024, and 2026.